Dakwah dan Hukum Lingkungan - Aripudin, Acep (Jurnal Ilmu Dakwah, 2008)
The most important of Central isue in global era is globalÂ  warning effect. One of itsâcauses isÂ  hyper-usingÂ  of technology un-controlled, that become damage in this world. The other causes is un-controlled ofÂ  exploitation to nature and is not be attend to ecosystem and environment live. Respons and reaction to global condition was spoken by a lot of people, --include â Islam, specially if looked according to Islamic law. Masalah-mursalah concept, as teoritic can be made basic inÂ  giving solutionÂ  this global accident.